Synthesis of Robust Control System Using Double-Mass Electro-Mechanical - O. F. Opeyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper describes conditions under which a single-mass model can be applied for system synthesis where elastic vibrations take place. This measure makes it possible to ensure the required indices of system quality without its structure complication. A small-parameter method is applied in the paper. A ratio of the required characteristic frequency of the synthesized system to own frequency of free vibrations of an elastic member is taken as a small parameter.The synthesized system is a robust (low-sensitive to changes of the object parameters) one. Results of mathematical modeling prove the possibility to ensure acceptable indices of quality and robustness of the synthesized system.